The influence of students’ knowledge on security towards their behavior with security risks within the context of Saudi Arabia - Ahmed, Aldossary Alia; Zeki, Akram M. (IEEE, 2014)
Information Security Awareness (ISA) is a considerable break in the wall of information security. People may show different level of awareness for security threats based on their knowledge, behavior and culture. In Saudi, studies showed that employees are less aware to security risks due to lack of knowledge and the demand culture. This paper presents the influence of students’ knowledge on their behavior with security risks particularly those are personally related to them such as risks of guessable passwords, email attachments, junk email, pirated software and hacking. This paper selected students from two Universities from the East of kingdom of Saudi Arabia.